Correlation of the tokamak H-mode density limit with ballooning stability at the separatrix. (15th January 2018) - Eich, T.; Goldston, R.J.; Kallenbach, A.; Sieglin, B.; Sun, H.J.
Abstract: We show for JET and ASDEX Upgrade, based on Thomson-scattering measurements, a clear correlation of the density limit of the tokamak H-mode high-confinement regime with the approach to the ideal ballooning instability threshold at the periphery of the plasma. It is shown that the MHD ballooning parameter at the separatrix position α s e p increases about linearly with the separatrix density normalized to Greenwald density, n e, s e p / n G W for a wide range of discharge parameters in both devices. The observed operational space is found to reach at maximum n e, s e p / n G W ≈ 0.4 –0.5 at values for α s e p ≈ 2 –2.5, in the range of theoretical predictions for ballooning instability. This work supports the hypothesis that the H-mode density limit may be set by ballooning stability at the separatrix.